Iraq, Imperialism, Political Economy, and International Law - Hammoudi, Ali (2019)
Iraq has had a unique, extraordinary, and contradictory historical relationship with international law and world order. From its inception as a modern and sovereign state in 1932, it was considered the pride of the new postwar order – a triumph of the “peaceful” workings of the international institution of the Mandate system of the League of Nations. By the first Gulf War in 1991 and later the 2003 invasion, it was labeled a “rogue” and “outlaw” state that needed to be put in its place by the “civilized” world through the instruments of war, economic sanctions, and unilateral invasion. This chapter will explore this contradictory relationship and its dynamics in history.
Keywords: Ali Hammoudi